Ticks (Acari: Ixodidae) on captive and free-ranging wild animals in Tocantins State, a Cerrado-Amazon transition region of northern Brazil. Issue 4 (18th May 2020) - Martins, Thiago F.; Reis, Juliane L.; Viana, Eduardo B.; Luz, Hermes R.; Oda, Fabrício H.; Dantas, Silionamã P.; Labruna, Marcelo B.
ABSTRACT: From January 2012 to August 2018, a total of 1013 specimens of ticks were collected and identified from 116 captive or free-ranging wild animals from Tocantins State, northern Brazil. The following tick-host associations were recorded: Amblyomma rotundatum Koch, 1844 on amphibians; Amblyomma cajennense sensu lato (Fabricius, 1787), Amblyomma humerale Koch, 1844 and A. rotundatum on reptiles; A. cajennense s. l. on bird; and Amblyomma auricularium (Conil, 1878), A. cajennense s. l., A. cajennense sensu stricto, Amblyomma dubitatum Neumann, 1899, Amblyomma geayi Neumann, 1899, Amblyomma naponense (Packard, 1869), Amblyomma nodosum Neumann, 1899, Amblyomma oblongoguttatum Koch, 1844, Amblyomma ovale Koch, 1844, Amblyomma pseudoconcolor Aragão, 1908, A. rotundatum, Amblyomma sculptum Berlese, 1888, Amblyomma tigrinum Koch, 1844, Haemaphysalis juxtakochi Cooley, 1946, Dermacentor nitens Neumann, 1897, Rhipicephalus microplus (Canestrini, 1887), and Rhipicephalus sanguineus sensu lato (Latreille, 1806) on mammalian hosts. The presence of A. dubitatum, A. naponense and H. juxtakochi in Tocantins is recorded for the first time.